2008
DOI: 10.1007/s11240-008-9465-y
|View full text |Cite
|
Sign up to set email alerts
|

Efficient regeneration of plantlets from callus and mesophyll derived protoplasts of Robinia pseudoacacia L.

Abstract: A protocol for plant regeneration from mesophyll and callus protoplasts of Robinia pseudoacacia L. was developed. For leaves from in vitro raised shoots, an enzyme combination of 2.0% cellulose and 0.3% macerozyme for a digestion period of 20 h resulted in the best yield of protoplasts (9.45 9 10 5 protoplast/g fresh weight). Mesophyll-derived protoplasts started cell wall regeneration within 24 h of being embedded in Nagata and Takebe (NT) medium supplemented with 5 lM NAA and 1 lM BAP followed by the first c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…In the present studies we found that roots developed on charcoal medium without any plant growth regulators. This promotive effect of a growth regulator free medium on in vitro root induction has been recorded in other trees such as Robinia pseudoacacia (Kanwar et al 2009) and Morus alba (Agarwal and Kanwar 2007). Plant Cell Tiss Organ Cult (2010) 100:199-207 205 Acclimatization of in vitro raised plantlets…”
Section: Influence Of Agno 3 On Shoot Bud Regenerationmentioning
confidence: 69%
“…In the present studies we found that roots developed on charcoal medium without any plant growth regulators. This promotive effect of a growth regulator free medium on in vitro root induction has been recorded in other trees such as Robinia pseudoacacia (Kanwar et al 2009) and Morus alba (Agarwal and Kanwar 2007). Plant Cell Tiss Organ Cult (2010) 100:199-207 205 Acclimatization of in vitro raised plantlets…”
Section: Influence Of Agno 3 On Shoot Bud Regenerationmentioning
confidence: 69%
“…Analysis of variance on protoplast viability (%; n = 3) in Lilium ledeoborii treatment had eventually reduced the number of viable protoplasts in the protoplast isolation of Crocus sativus L. (Darvishi et al, 2006). In contrast, a digestion period of up to 20 h resulted in the best yield of protoplasts (9.45 × 10 5 protoplasts/g FW) from the callus tissue of the nitrogen fixing woody plant, Robinia pseudoacacia (Kanwar et al, 2009). It's concluded that, the best treatment for isolation of Lilium protoplast was 4% cellulase and 1% pectinase for 24 h.…”
Section: Methodsmentioning
confidence: 93%
“…For plant regeneration from protoplast-derived callus, we used media supplemented with combinations of either NAA and BAP, or NAA and zeatin. NAA and BAP induce shoot regeneration from protoplast cultures of K. blossfeldiana (Castelblanque et al 2010) and Robinia pseudoacacia (Kanwar et al 2009). Zeatin is frequently combined with NAA and used in protoplast regeneration protocols for shoot induction e.g.…”
Section: Discussionmentioning
confidence: 99%